Elit sporcularin yeni tip koronavirüse (COVID-19) yakalanma kaygi durumlarinin incelenmesi - Yildiz, Y. (International Journal of Human Sciences, 2020)
The aim of this study is to examine of the anxiety situations of catching the new type of coronavirus (COVID-19) in elite athletes. The research group consisted of individuals who actively exercise at the elite level. This study has parcipated 151 athletes. In order to measure the anxiety levels of the athletes, was used the New Type Coronavirus (COVID-19) Anxiety Scale (SYTKYKÖ) of the Athletes, whose validity and reliability analysis was performed by Tekkursun Demir et al. (2020). The analysis of the data obtained was evaluated in the SPSS 23 package program. Athletes participating in the study were 99 (65.6%) team sports (football 26, basketball 7, volleyball 46, handball 20) and 52 (34.4%) individual sports (athletics 17, taekwondo 13, swimming 9, wrestling 9, tennis 4). The athletes participating in the study 73.5% stated that they exercise at home 7.9% stated that they did not exercise at all, 3.3% did exercise in the field and 15.2% stated that they exercised both at home and in the field. In study 42.4% of team athletes and 13.2% of individual athletes "The league should be registered as it is now", 9.9% of team athletes, 7.3% of individual athletes "should continue with the normalization process of the league and 13.2% of team athletes and 13.9% of individual athletes replied that "the league should continue at a later date and the competitions should be completed". A significant difference was found at the p <0.05 level in the individual anxiety subdimension according to the team athletes and individual athletes. No significant difference was found in socialization anxiety scores. As a result; The vast majority of elite athletes state that the leagues should be vacationed or registered during the pandemic process and that it is necessary to exercise at home during this period. In addition, it was determined that the anxiety scores of those who expressed their opinion in the form of playing or registering the leagues at a later date, according to individual anxiety and socialization anxiety.